Construction of a nomogram based on disinfection methods and clinical characteristics of ICU patients to forecast hospital-acquired respiratory infections: A single-center study from China - Congjie Zhang; Yiyuan Zhang; Changyuan Quan; Xiaotao Lai; Sheng Ming; Hemin Zhang; Haiqun Wu; Fangfang He (PLoS ONE, 2025)
Background Hospital-acquired respiratory tract infections (HARTI) are increasingly recognized by healthcare workers, especially among critically ill patients who are particularly susceptible. The selection of effective surface disinfectants can effectively block the transmission of pathogens, with chlorine-based disinfectants being widely used at present. This study constructs a nomogram by analyzing the choice of surface disinfection methods and clinical information of patients, to predict the occurrence of HARTI in ICU patients. Method This study collected 592 patients admitted to the ICU from 01/01/2020–31/12/2023, and used binary logistic regression analysis to predict the predictive effect of Malignant tumor, Admission ICU unit, CRP, APTT, Any norepinephrine use, Blood.transfusion, Chlorine disinfectant, Tracheotomy on the occurrence of HARTI in ICU patients. And use R studio to construct nomogram model. Result The results indicate that MONO (7.16[2.16,23.71]), BUN (0.24[0.06,0.88]), SOFA (4.5[1.48,13.74]), chlorine disinfectant (500 mg/L) (0.02[0,0.07]) in the choice of disinfection method, and bed railing (0.14[0.04,0.48]), micro-infusion pump (0.31[0.1,0.98]) in the area of disinfection are independent predictors of HARTI occurrence. The nomogram derived from the study demonstrated good predictive performance and showed minor errors in both the training and validation sets, providing significant clinical benefits to most patients. Subgroup analysis also well demonstrated this point, showing that it can better reduce the occurrence of HARTI patients in the ICU compared to two other types of disinfectants. Conclusion Regulation of MONO and BUN values in blood indicators for ICU patients, intervention on corresponding indicators in the SOFA score, and the use of Chlorine disinfectant (500 mg/L) for surface disinfection, with a focus on disinfecting bed railings and micro-infusion pumps, can significantly reduce the incidence of HARTI, allow for early prevention and adjustment of HARI, and simultaneously benefit more patients.